PEMBUATAN SOAL ASSESMEN KOMPETENSI MADRASAH INDONESIA (AKMI): TEORI DAN PRAKTEK BAGI GURU MI - Faizah, Maryam; Bisriyah, Maslihatul; Hasanah, Siti Ma’rifatul (JRCE (Journal of Research on Community Engagement), 2022)
The implementation of the National Assessment which includes the Minimum Competency Assessment (AKM), Character Survey, and Learning Environment Survey is considered a challenge for both teachers and schools/madrasahs. Therefore, it is necessary to train teachers to prepare themselves for the implementation of this new assessment system. This community service aims to provide training for madrasah teachers regarding creating the questions. The 50 participants of the activity were teachers from Madrasah Ibtidaiyah (MI) who were members of the Group of Teachers of Madrasah Ibtidaiyah (KKG MI) Kepanjen District. This program carried out face-to-face while still applying health protocols. The results of this program show that understanding the AKMI concept and preparing questions requires intensive assistance and a long period of time. Because it is improving teachers’ skills, each participant can do individual coaching with the presenter